Teacher-students’ relationship and the learning of the english language with the students of the 8th year of basic education at unidad educativa San Francisco de Asís of Loja city, academic year 2013-2014 - Granda Jiménez, Rita Isabel (2015)
The thesis entitled: TEACHER-STUDENTS´ RELATIONSHIP AND THE LEARNING OF THE ENGLISH LANGUAGE WITH THE STUDENTS OF THE 8TH YEAR OF BASIC EDUCATION AT UNIDAD EDUCATIVA SAN FRANCISCO DE ASÍS OF LOJA CITY, ACADEMIC YEAR 2013-2014, has as its main objective to determine how the Relationship teacher–students’ influences the English language learning improvement with the students of 8th year of Basic Education at Unidad Educativa San Francisco de Asis The methods applied in this research were: scientific, analytic-synthetic, descriptive, statistical and explicative. Surveys were applied to teachers and students aiming to carry out the hypotheses verification through logical and statistical analysis represented in graphics and charts. The obtained results showed that teachers have a limited knowledge about the role of mediators they should play within the teaching learning–process, deficient strategies to gain their students’ confidence and respect. In spite of having the institutional Welfare Code, where regulations regarding students, teachers, parents and institutional authorities are expressed with a wide range of implications concerning the attitudinal formation of the students in the institution, it has not been socialized. This circumstance denotes a weakness that limits the strengthening of the educational actors’ behavior.